Mathematical ideas in early Philippine society posthumous essay - Manapat, Ricardo (Quezon City Ateneo de Manila University, 2011)
"This essay is a preliminary effort in outlining a history of mathematics in the Philippines. It calls attention to the existence of a highly developed enumeration and arithmetical system prior to the Spanish conquest, and argues that this enumeration system had unique characteristics that distinguised it from other Southeast Asian societies. Other mathematical and scientific ideas, such as the use of geometric concepts and astronomonical tools, in the preconquest Philippines are also discussed and presented."
Keywords: Mathematics -- Philippine history; Ethnomathematics